Cloud Technologies in Healthcare Supply Chains: Ensuring Efficiency and Transparency - Arjunkumar Vijayakumar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of cloud technologies in healthcare supply chains has revolutionized the management of critical medical supplies and temperature-sensitive products. This transformation encompasses comprehensive solutions for cold chain management, supplier collaboration, and logistics optimization. Cloud-based systems have enabled healthcare organizations to achieve remarkable improvements in inventory accuracy, order processing efficiency, and regulatory compliance. Through advanced IoT sensor networks and real-time monitoring capabilities, healthcare facilities have enhanced their ability to maintain temperature-sensitive pharmaceuticals within critical thresholds. The implementation of predictive analytics and AI-driven optimization has transformed delivery logistics, particularly benefiting underserved areas. Modern supplier collaboration platforms featuring multi-tenant architectures have streamlined procurement processes and enhanced communication efficiency. Looking ahead, quantum computing integration and 5G network deployment are positioned to further transform healthcare supply chains, while robust security protocols and blockchain-based compliance automation ensure data protection. These technological advancements have resulted in substantial reductions in operational costs, improved inventory accuracy, decreased product wastage, and enhanced overall healthcare delivery efficiency.